Pentapeptide cRGDfK-Surface Engineered Nanostructured Lipid Carriers as an Efficient Tool for Targeted Delivery of Tyrosine Kinase Inhibitor for Battling Hepatocellular Carcinoma - Deepak P; Kumar P; Pandey P; Arya DK; Jaiswal S; Kumar A; Sonkar AB; Ali D; Alarifi S; Ramar M; Rajinikanth PS (International Journal of Nanomedicine, 2023)
Payal Deepak,1 Praveen Kumar,2,3 Prashant Pandey,1 Dilip Kumar Arya,1 Shweta Jaiswal,1 Anand Kumar,1 Archana Bharti Sonkar,1 Daoud Ali,4 Saud Alarifi,4 Mohankumar Ramar,5 P S Rajinikanth1 1Department of Pharmaceutical Sciences, Babasaheb Bhimrao Ambedkar University, Lucknow, Uttar Pradesh, India; 2Department of Pharmacy, Indira Gandhi National Tribal University, Amarkantak, Madhya Pradesh, India; 3S.D College of Pharmacy and Vocational Studies, Muzaffarnagar, Uttar Pradesh, India; 4Department of Zoology, College of Science, King Saud University, Riyadh, 11451, Saudi Arabia; 5Department of Pharmacology and Toxicology, School of Pharmacy, University of Connecticut, Storrs, CT, 02903, USACorrespondence: P S Rajinikanth, Department of Pharmaceutical Sciences Babasaheb Bhimrao Ambedkar University, Lucknow, Uttar Pradesh, 226025, India, Email psrajinikanth222@gmail.comBackground: Antitumor research aims to efficiently target hepatocarcinoma cells (HCC) for drug delivery. Nanostructured lipid carriers (NLCs) are promising for active tumour targeting. Cell-penetrating peptides are feasible ligands for targeted cancer treatment.Methods: In this study, we optimized gefitinib-loaded NLCs (GF-NLC) for HCC treatment. The NLCs contained cholesterol, oleic acid, Pluronic F-68, and Phospholipon 90G. The NLC surface was functionalized to enhance targeting with the cRGDfK-pentapeptide, which binds to the αvβ 3 integrin receptor overexpressed on hepatocarcinoma cells.Results: GF-NLC formulation was thoroughly characterized for various parameters using differential scanning calorimetry and X-ray diffraction analysis. In-vitro and in-vivo studies on the HepG2 cell line showed cRGDfK@GF-NLC’s superiority over GF-NLC and free gefitinib. cRGDfK@GF-NLC exhibited significantly higher cytotoxicity, growth inhibition, and cellular internalization. Biodistribution studies demonstrated enhanced tumour site accumulation without organ toxicity. The findings highlight cRGDfK@GF-NLC as a highly efficient carrier for targeted drug delivery, surpassing non-functionalized NLCs. These functionalized NLCs offer promising prospects for improving hepatocarcinoma therapy outcomes by specifically targeting HCC cells.Conclusion: Based on these findings, cRGDfK@GF-NLC holds immense potential as a highly efficient carrier for targeted drug delivery of anticancer agents, surpassing the capabilities of non-functionalized NLCs. This research opens up new avenues for effective treatment strategies in hepatocarcinoma. Keywords: nanostructured lipid carrier, αvβ 3 integrin receptor, cRGDfK-pentapeptide, hepatocellular carcinoma, tumour targeting